Project Multatuli Feat Lembaga Pers Mahasiswa: Implementasi Jurnalisme Kolaborasi dalam Pemberitaan Kasus Kekerasan Seksual - Nur Cholisah, Alfida; Briyan Pratiwi, Rhesa Zuhriya (UIN Raden Mas Said Surakarta, 2024)
The increasing of sexual violence cases in Higher Education has made Project Multatuli, a non-profit alternative media based on public journalism, with the Student Press to conduct collaborative journalism to highlight this. Through the implementation of the Journalistic Code of Ethics with a survivor's perspective, the collaborative journalism that’s formed is a means for the Student Press together with professional journalists to contribute to voicing cases of sexual violence on campus. This article aims to describe the implementation of collaborative journalism, by Project Multatuli together with LPM Institut, LPM Bhaskara, and Pers Akademika related to news coverage of sexual violence on campus. The type of research is descriptive qualitative, with data collection through observation, in-depth interviews, and documentation. Data analysis is carried out interactively, with data validity through source triangulation. Data findings describe collaborative journalism that’s temporary and integrated. The implementation of collaborative journalism is carried out through investigative reporting with a victim's perspective; providing security for survivors, journalists, and the media; prioritizing the victim's point of view and consent in reporting; including actively informing survivors about the risks of coverage.